Modelling of thin layer drying kinetics of sour cherry in a solar dryer and under open sun - Akpinar, E. Kavak; Bicer, Y. (Natl Inst Science Communication-Niscair, 2007)
Drying kinetics of sour cheery is investigated in solar dryer with forced convection and under open Sun with natural convection. Drying data were fitted to different mathematical models, whose performance was investigated by comparing coefficient (R), reduced chi-square (C-2) and root mean square error (RMSE) between the observed and predicted moisture ratios. Among these models, drying model developed by Midilli and Kucuk model showed good agreement with the data obtained from the experiments in the solar dryer with forced convection drying mode. Logarithmic model has shown a better fit to the experimental sour cherries data for open sun drying with natural convection mode than the other models.
Keywords: forced drying; solar drying; sour cherry; Thin layer drying models